ANALISIS UDARA AMBIEN POLUTAN CO KENDARAAN BERMOTOR TERHADAP TUTUPAN LAHAN DI LINGKUNGAN UNIVERSITAS LAMPUNG - Hamzah, Budi; Sulistiyorini, Rahayu; Putri Ofrial, Siti Anugrah; Herianto, Dwi (Universitas Lampung, 2023)
This study aims to see the effect of the number of vehicles on the amount of Carbon Monoxide (CO) emissions in the University of Lampung environment after there is land cover and the amount of ambient air concentration of Carbon Monoxide (CO) Pollutants in the University of Lampung environment after there is land cover. The location of this study is at the University of Lampung, the stages of data collection in this study are carried out in two stages, namely primary data collection and secondary data collection, then analyzed through complications and tabulation activities as well as analysis of air quality levels at the University of Lampung after land cover. The results of research and data analysis show that overall the air quality of Carbon Monoxide (CO) in the University of Lampung environment after land cover is in the good category because it has a range of air pollution between 1 - 50 according to air quality standards set by the government through regulations. Minister of Environment and Number P.14/MENLHK/SETJEN/KUM.1/7/2020 concerning Air Pollutant Standard Index.CO concentration is still at the threshold value required by Government Regulation Number 41 of 1999 concerning ambient air quality standards even though most of the land in the University of Lampung is land cover. Key words : Ambient Air, Carbon Monoxide (CO), Land Cover.